A study of hardware implementations of the CRC computation algorithms - Mytsko E. A. Evgeniy Aleksandrovich; Malchukov A. N. Andrey Nikolaevich; Ryzhova S. E. Svetlana Evgenievna; Kim V. L. Valery Lvovich (Information and Telecommunications Technologies, 2016)
Title screen